The Optimization of the Woodlam Furniture Factory with Specific Reference to It’s Electricity Consumption - Wagener, R. (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2017.